2017
DOI: 10.1152/ajpheart.00046.2017
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of passive hindlimb cycling and active upper-limb exercise provides new insights into systolic dysfunction after spinal cord injury

Abstract: Active upper-limb and passive lower-limb exercise are two interventions used in the spinal cord injury (SCI) population. Although the global cardiac responses have been previously studied, it is unclear how either exercise influences contractile cardiac function. Here, the cardiac contractile and volumetric responses to upper-limb (swim) and passive lower-limb exercise were investigated in rodents with a severe high-thoracic SCI. Animals were divided into control (CON), SCI no exercise (NO-EX), SCI passive hin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
29
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 63 publications
4
29
0
Order By: Relevance
“…It is important to note, however, that rodents with a MODERATE T3 contusion injury recover some weight-bearing stepping (Squair et al 2017b), and are therefore likely to maintain their preload, in part, through muscle-pump-mediated increases in flow back to the heart. Although this is likely to contribute to the maintenance of SV, we do not believe it contributes to the maintenance of radial strain and contractile function in our MODERATE group, as we have previously found that hindlimb exercise can improve only stroke volume and not systolic contractile function (DeVeau et al 2017). In fact, the only intervention we have found that normalizes contractile function post-SCI is dobutamine, a specific β 1 -agonist (Squair et al 2017a).…”
Section: Discussionmentioning
confidence: 62%
See 3 more Smart Citations
“…It is important to note, however, that rodents with a MODERATE T3 contusion injury recover some weight-bearing stepping (Squair et al 2017b), and are therefore likely to maintain their preload, in part, through muscle-pump-mediated increases in flow back to the heart. Although this is likely to contribute to the maintenance of SV, we do not believe it contributes to the maintenance of radial strain and contractile function in our MODERATE group, as we have previously found that hindlimb exercise can improve only stroke volume and not systolic contractile function (DeVeau et al 2017). In fact, the only intervention we have found that normalizes contractile function post-SCI is dobutamine, a specific β 1 -agonist (Squair et al 2017a).…”
Section: Discussionmentioning
confidence: 62%
“…Although we cannot specifically rule this out, we believe it is unlikely to be the principal cause of our between-group differences, as we have shown that upper limb exercise alone (i.e. swim training) exerts no influence on contractile cardiac function (DeVeau et al 2017). It is important to note, however, that rodents with a MODERATE T3 contusion injury recover some weight-bearing stepping (Squair et al 2017b), and are therefore likely to maintain their preload, in part, through muscle-pump-mediated increases in flow back to the heart.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Dobutamine is a sympathomimetric drug and has been used previously following SCI to increase the chronotrophy and inotrophy of the heart (DeVeau et al. , ; Squair et al. ).…”
Section: Methodsmentioning
confidence: 99%